Bollworm control with pheromones - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Work at the Central Cotton Research Institute in Pakistan has shown that using sex pheromones to disrupt cotton bollworm mating may offer a non-toxic alternative to chemical control. Three bollworm species, Pectinophora gossypiella, Earias vittella...